World kidney day fun run 2023 / Qayyim Fakhriy and Adilah Natasya - Fakhriy, Qayyim; Natasya, Adilah (Universiti Teknologi MARA, Negeri Sembilan, 2023)
The World Kidney Fun Run 2023 is a collaborative program between UiTM Negeri Sembilan and the National Kidney Foundation of Malaysia, the Nephrology Society of Malaysia, the Department of Nephrology, and The Competitive Sports Department. This fun run program took place at Dataran Nilai, Negeri Sembilan with a total of almost 125 participants. The purpose of this program was to raise awareness among the community about the importance of our kidneys. As we can see, the community is increasingly making themselves aware of their health regardless of the cost as long as they stay healthy and lead a good healthy lifestyle. The goal of the management is not only to set kidney care as the main objective but also to highlight the importance of body care and being properly diagnosed for diseases that may damage the body's systems. In addition, the program was to also aid those suffering from kidney cancer by creating further awareness of the disease.